(untitled) (Revista Iberoamericana de Bioética, 2025)
This study explored perceptions of bioethics, gender, and sexual diversity within the academic community of the Faculty of Biological Pharmaceutical Chemistry at Universidad Veracruzana, Xalapa. Through an online survey applied to students and faculty, attitudes and knowledge regarding the integration of gender perspective and the inclusion of sexual diversity in professional training were analyzed. The results show a broad awareness of the importance of these issues, with greater openness among younger generations and faculty members, although cases of discrimination and more conservative positions persist in certain groups. The findings highlight the need to strengthen bioethical education in biomedical and pharmaceutical sciences through inclusive approaches that promote equality and justice. This work provides empirical evidence to guide university and curricular policies toward more respectful and diverse academic communities.